AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KELOR (Moringa oleifera L.) TERHADAP Staphylococcus aureus ATCC 43300 - Wuga, Kristina Supartin Monika; Jawi, I Made; Artini, I Gusti Ayu; Widhiartini, Ida Ayu Alit (E-Jurnal Medika Udayana, 2024)
Background: Kelor leaves (Moringa oleifera L.) have active compounds such as flavonoid, alkaloid, phenol, tanin, and saponin. The content of these compounds is stated to have antibacterial activity. the development of an alternative treatment of natural ingredients is needed to treat infections caused by Staphylococcus aureus bacteria, one of which is Moringa leaves (Moringa oleifera L.). Objective: To analyze the antibacterial activity from ethanol extract of moringa leaf in inhibiting of Staphylococcus aureus growth at concentrations of 25%, 50%, and 100%. Methods: The method used is a true experimental posttest-only control group in vitro. The samples of this study were divided into five groups: the positive control group (vancomycin) and the negative control group (96% ethanol solvent), with concentrations of 25%, 50%, and 100%. Result: The results proved that the extract of ethanol from moringa leaves without dilution (100% of concentration) showed about zone of inhibition against Staphylococcus aureus ATCC 43300 bacteria with an inhibition diameter of 8.4 mm and the positive control vancomycin has an inhibition zone diameter of 17.4 mm. Conclusion: Moringa leaf ethanol extract showed inhibition against bacterial growth in vitro at a concentration of 100%. Keywords: Antibacterial activity, Moringa oleifera L, Staphylococcus aureus